Acute encephalitis associated with SARS-CoV-2: first case report in Peru - Barreto-Acevedo, Elliot (2020)
In the context of the COVID-19 pandemic, atypical clinical forms have been described, in which extra-respiratory symptoms predominate; among them, cases of concurrent neurological manifestations have been reported. Based on the coronavirus identification in the central nervous system in the 2002 SARS-CoV outbreak, a potential neurotropism of SARS-CoV-2 has been raised. Few patients with acute encephalitis associated with SARS-CoV-2 have been described in the world literature. In this report we present two cases of Peruvian patients with acute encephalitis concurrent to COVID-19, we reviewed the literature and discussed the possible mechanisms of neurotropism and neuroinvasion.